1996
DOI: 10.1111/j.1540-8159.1996.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Endocardial Pacing Lead Body Migration Compromising Fontan Physiology

Abstract: Migration of intracardiac transvenous pacing leads may occur. There is a known risk of intrapulmonary ventricular pacing lead migration in patients with endocardial lead systems. In the current report we present the late intrapulmonary migration of an endocardial atrial pacing lead body. The patient had undergone antitachycardia pacemaker placement to control recurrent atrial tachyarrhythmias following the Fontan procedure. Although the lead electrode remained in place and continued to pace, the lead body migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A previous case report indicated that a migrated pacing lead deteriorated hemodynamics for an extended period of time following surgery. 3 In a previous hospital, the current patient's echocardiogram showed moderate TR and the cardiologists reported a clear TR murmur. Two months later, when she was admitted to our hospital, we heard little TR murmur and the echocardiogram performed in our hospital supported our auscultation, which was only mild regurgitation.…”
Section: Discussionmentioning
confidence: 74%
“…A previous case report indicated that a migrated pacing lead deteriorated hemodynamics for an extended period of time following surgery. 3 In a previous hospital, the current patient's echocardiogram showed moderate TR and the cardiologists reported a clear TR murmur. Two months later, when she was admitted to our hospital, we heard little TR murmur and the echocardiogram performed in our hospital supported our auscultation, which was only mild regurgitation.…”
Section: Discussionmentioning
confidence: 74%